Wendell Berry and Higher Education : Cultivating Virtues of Place - Baker, Jack R.; Bilbro, Jeffrey (Book collections on Project MUSE., 2017)
Prominent author and cultural critic Wendell Berry is well known for his contributions to agrarianism and environmentalism, but his commentary on education has received comparatively little attention. Drawing on Berry's essays, fiction, and poetry, Jack R. Baker and Jeffrey Bilbro illuminate the influential thinker's vision for higher education in this groundbreaking study.